Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae) - Terzani, Fabio; Ceccolini, Filippo; Hájek, Jiří; Cianferoni, Fabio (Zootaxa, 2017)
The genus Dascillus Latreille, 1797 in the Western Palaearctic is reviewed by examination of nearly 1,000 specimens, predominantly from Italy, but also other European and Western Asian countries. The study of external morphology and male genitalia shows high variability in all previously used diagnostic characters, which does not enable unambiguous characterisation of currently recognised species. Therefore, we retain a single valid species in the Western Palaearctic—Dascillus cervinus (Linnaeus, 1758) of which we designate the lectorype, and establish its following new synonymies: Dascillus sicanus Fairmaire, 1861 syn. nov., Atopa elongata Faldermann, 1835 syn. nov. Consequently, the following taxa previously synonymised with Dascillus elongatus (D. elongatus var. obscuricollis Pic, 1908 and D. elongatus var. ruficollis Pic, 1908) and D. sicanus (D. parallelus Dohrn, 1872 and D. aprutianus Depoli, 1936) are now considered as synonyms of D. cervinus as well. First records of D. cervinus for Albania, Bosnia and Herzegovina, Macedonia, Montenegro, and some Italian regions are given.